2016
DOI: 10.1103/physrevc.94.034310
|View full text |Cite
|
Sign up to set email alerts
|

Shell-model configuration-interaction description of quadrupole collectivity in Te isotopes

Abstract: We present systematic calculations on the spectroscopy and transition properties of even-even Te isotopes by using the large-scale configuration interaction shell model approach with a realistic interaction. These nuclei are of particular interest since their yrast spectra show a vibrational-like equally-spaced pattern but the few known E2 transitions show anomalous rotational-like behavior, which cannot be reproduced by collective models. Our calculations reproduce well the equallyspaced spectra of those isot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The calculation was performed with the program KSHELL. It was shown that the calculations reproduce well the excitation energies and E2 transition probabilities in even-even Te isotopes [89,90]. 131 Xe.…”
Section: B Shell-model Calculationsmentioning
confidence: 68%
“…The calculation was performed with the program KSHELL. It was shown that the calculations reproduce well the excitation energies and E2 transition probabilities in even-even Te isotopes [89,90]. 131 Xe.…”
Section: B Shell-model Calculationsmentioning
confidence: 68%
“…A renormalization was performed by a perturbative G matrix approach to include core-polarization effects. It was shown that the calculations reproduce well the excitation energies and E2 transition probabilities in even-even Te isotopes [64,65].…”
Section: Discussionmentioning
confidence: 78%
“…In 129 Sn the seniority v = 3 multiplet is completed by the J π = (27/2 − ) state at E x = 2552 keV [T 1/2 = 0.27 (7) μs], identified by Lozeva et al in 2008 [4]. 131 Te was populated in a pioneering 64 Ni + 130 Te multinucleon-transfer experiment at the GASP γ -ray spectrometer [10]. A delayed 361-564-833-keV triple-γ coincidence was identified to form the (21/2 − ) → (19/2 − ) → (15/2 − ) → 11/2 − yrast band.…”
Section: Introductionmentioning
confidence: 99%
“…Moving to heavier nuclei, the effective charges in the 132 Sn region are near the default values [62], although most recent calculations adopt e p ≈ 1.7e and e n ≈ 0.8e [32,34,63,64]. The measured B(E2) for 130 Sn [46,47] is lower than theory and the experimental systematics (see [65]); the experiment should be repeated.…”
Section: Nuclidementioning
confidence: 99%